Reflexões sobre o processo de aprender: efeitos de estratégias de aprendizagem para alunos de língua inglesa em contexto universitário - Almeida, Elom de Paulo Andrade de (Universidade Federal de São Carlos, 2024)
The variety of resources available for language learning has offered students the opportunity to become autonomous in this process. However, even with access to these tools, it is possible that these learners do not know how to manage and guide their studies, something that the application of learning strategies (EAs) can facilitate. The objective of this study is to investigate the use of EAs by English language students in an extension course offered through the Language Institute of a public university and the implications of managing these strategies in the formation of students' autonomy during the course. Above all, we seek to verify the use of these strategies, which ones are used and how students apply them in order to manage their learning process. The theories underlying this work are related to studies by Oxford (1990, 2017, 2021), Griffiths (2018) and Cohen (2014). The research is based on a qualitative, ethnographic-based approach, with the researcher as a participant observer in the role of teacher and the use of questionnaires and reflective diaries as data collection instruments. As a result, we identified that all participants demonstrate using strategies, but with different variations and nature, in addition to applying them in chains or clusters. Regarding the effects on the formation of autonomous learners, we found that instruction on learning strategies and the writing of reflective journals contributed to the awareness of how to act and how to regulate the way of learning, as well as the recognition of their active role in the learning process.
Reflections on the learning process: effects of learning strategies for english language students in a university context
Keywords: Aprendizagem de línguas; Estratégias de aprendizagem; Autonomia; Língua inglesa; Contexto universitário; Language learning; Learning strategies; Autonomy; English as a foreign language; University context; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA